9m-15=66

Simple and best practice solution for 9m-15=66 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9m-15=66 equation:


Simplifying
9m + -15 = 66

Reorder the terms:
-15 + 9m = 66

Solving
-15 + 9m = 66

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '15' to each side of the equation.
-15 + 15 + 9m = 66 + 15

Combine like terms: -15 + 15 = 0
0 + 9m = 66 + 15
9m = 66 + 15

Combine like terms: 66 + 15 = 81
9m = 81

Divide each side by '9'.
m = 9

Simplifying
m = 9

See similar equations:

| 4(2p-2)=3(2p+4) | | -3(2-1x)=2x-9 | | 2=-2y+6/13 | | 10y=-5x-15 | | 11x=-42 | | 3+log[4](x+6)=4 | | 0.12x^2-0.72x-0.137=0 | | 100x+100x^2-45=0 | | 2014-1952+-7abc+18=62 | | -2(3x-4)=-(2x-2) | | 0.12x^2+-0.72x+-0.137=0 | | 20x-24=2x | | -11=7-1x | | 45g+7=-6 | | x^3-(2x^2)+1.25x-0.25=0 | | 1952-7abc+18=62 | | 2+2k=8k+3-6k | | x^3-(2x^2)+1.5x-0.25=0 | | 5n-8=n+27 | | [9(y+5)-17]-[3(y-4)+3]= | | 5x-3+7x=45 | | 2+2k=8k+3-6 | | 2(x-2)=3x-4x+5 | | 2x+10=6x-4 | | 7-3(3)=-3+1 | | 17.50-8.75= | | (n+4)-(-3n-7)= | | k/15-13=4 | | 7k^2-54k-16= | | [7(z+5)-17]+[3(z-2)+2]= | | 19abc+18=62 | | 3t=3r-54 |

Equations solver categories